Competitive Screening Under Heterogeneous Information. (19th December 2018) - Garrett, Daniel F; Gomes, Renato; Maestri, Lucas
Abstract: We study the interplay between informational frictions and second-degree price discrimination. Our theory recognizes that consumers differ in their tastes for quality as well as in the information they possess about available offers, which leads to dispersion over price–quality menus in equilibrium. While firms are ex ante identical, we show that their menus are ordered so that more generous menus leave more surplus to consumers of all valuations. We explore the cross-section of equilibrium menus and variations in market conditions to generate empirical predictions on prices, qualities, and markups across firms, and within a firm's product line. For instance, more competition may raise prices for low-quality goods; yet, consumers are better off, as the qualities they receive also increase. The predictions of our model illuminate empirical findings in many markets, such as those for cell phone plans, yellow-pages advertising, cable TV, and air travel.